2022
DOI: 10.1038/s41467-022-29124-8
|View full text |Cite
|
Sign up to set email alerts
|

Opposite physiological and pathological mTORC1-mediated roles of the CB1 receptor in regulating renal tubular function

Abstract: Activation of the cannabinoid-1 receptor (CB1R) and the mammalian target of rapamycin complex 1 (mTORC1) in the renal proximal tubular cells (RPTCs) contributes to the development of diabetic kidney disease (DKD). However, the CB1R/mTORC1 signaling axis in the kidney has not been described yet. We show here that hyperglycemia-induced endocannabinoid/CB1R stimulation increased mTORC1 activity, enhancing the transcription of the facilitative glucose transporter 2 (GLUT2) and leading to the development of DKD in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 103 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…Although no previous studies have demonstrated that c-Maf is a major transcription factor regulating the expression of glucose transporters in kidney proximal tubules, we found that c-Maf directly regulates Sglt2 and Glut2 , which are responsible for the reabsorption of renally filtered glucose in proximal tubules. It has previously been reported that the transcription factors Hnf1α, Hnf3β, and Srebp1c link Sglt2 expression ( 20 , 22 , 58 , 59 61 ), while Hnf4α-mutant mice present with renal glycosuria due to the loss of Sglt2 ( 61 , 62 ). Furthermore, Sp1 has been shown to promote Sglt1 and Sglt2 expression in the presence of Zn ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no previous studies have demonstrated that c-Maf is a major transcription factor regulating the expression of glucose transporters in kidney proximal tubules, we found that c-Maf directly regulates Sglt2 and Glut2 , which are responsible for the reabsorption of renally filtered glucose in proximal tubules. It has previously been reported that the transcription factors Hnf1α, Hnf3β, and Srebp1c link Sglt2 expression ( 20 , 22 , 58 , 59 61 ), while Hnf4α-mutant mice present with renal glycosuria due to the loss of Sglt2 ( 61 , 62 ). Furthermore, Sp1 has been shown to promote Sglt1 and Sglt2 expression in the presence of Zn ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of mesangial matrix expansion, tubulointerstitial fibrogenesis, and the number of WT1 positive nuclei were assessed by measuring the PAMS-and mesangial Sirius Redpositive areas, and by performing IHC staining for WT1 in the kidneys. PAMS-stained glomeruli (20-25 fields at 40× magnification), Sirius Red-stained interstitial lesions (20)(21)(22)(23)(24)(25)(26)(27) fields at 20× magnification), and the number of WT1-positive nuclei (15-20 fields at 40× After centrifugation at 2,000 rpm for 5 min at 4 °C, the supernatant was discarded and the antibody-protein-DNA complexes were washed twice with a high salt wash buffer (20 mM Tris-HCl [pH 7.9], 500 mM NaCl, 2 mM EDTA, 1% Triton X-100, and 0.1% SDS), once with LiCl wash buffer (10 mM Tris-HCl [pH 7.9], 250 mM LiCl, 1 mM EDTA, 1% NP-40, and 1% sodium deoxycholate), and twice with Tris-EDTA (pH 7.9). The samples were then incubated in an elution buffer (100 mM NaHCO3, 1% SDS, and 10 mM dithiothreitol (DTT) at about 25 °C for 15 min, centrifuged at 2,000 rpm for 1 min at about 25 °C, and the was collected.…”
Section: Measurement Of Periodic Acid-methenamine Silver (Pams)-and S...mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been over 18,000 DN-related manuscripts published since the beginning of the 21 st century corresponding to a diverse array of topics including DN-related drug therapy [ 24 26 ], the pathology and pathophysiology of DN [ 27 ], the diagnosis of DN [ 28 , 29 ], the etiology of DN [ 30 , 31 ], and the epidemiology of DN [ 32 , 33 ]. Given the complexity and density of information published in this field over the past two decades, there is a clear need for a systematic and objective approach to surveying DN-related research directions.…”
Section: Discussionmentioning
confidence: 99%
“…There have been over 18,000 DN-related manuscripts published since the beginning of the 21 st century corresponding (1) Drug therapy of DN 58, 33,4,36,25,15,41,51,13,18,59 (1) Single-gene polymorphism of DN (2) Dialysis on DN 27,11,32,40,57,43,20,12,30,50,56,55 (1) Physiopathology of DN (2) Metabolism of DN 45,42,35,53,48,24,2,26,22,34,49,23,8,37 (1) Podocyte metabolism in DN (2) Signal transduction of DN (3) MicroRNAs of DN (4) Mesangial-cell metabolism in DN 9 Oxidative Medicine and Cellular Longevity to a diverse array of topics including DN-related drug therapy [24][25][26], the pathology and pathophysiology of DN [27], the diagnosis of DN [28,29], the etiology of DN [30,31], and the epidemiology of DN [32,…”
Section: Discussionmentioning
confidence: 99%